2015
DOI: 10.1037/rep0000045
|View full text |Cite
|
Sign up to set email alerts
|

Beyond depression: Predictors of self-reported cognitive function in adults living with MS.

Abstract: Objective To investigate the association between self-reported cognition and demographic/psychosocial variables in individuals with a self-reported diagnosis of multiple sclerosis (MS). Design Secondary longitudinal analysis of mailed self-report surveys over a period of 2 years. Setting Community. Participants 407 community-dwelling individuals from the Pacific Northwest with a self-reported diagnosis of MS. Interventions Not applicable. Main Outcome Measures Subjective general cognitive concerns an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 61 publications
5
29
0
Order By: Relevance
“…47 The significant relation between cognitive complaints and anxiety in MS patients is also in line with earlier findings and might be part of the above relation between anxiety and depression. 48 However, whether cognitive complaints contribute to anxiety or the other way around cannot be answered on the basis of our cross-sectional data. 25,35 Moreover, in a longitudinal study, 48 the authors showed that anxiety and fatigue were significant predictors of general cognitive concerns during a 2-year follow-up.…”
Section: Ms Population a Biological Hypothesis For The Overlap Betwementioning
confidence: 84%
See 1 more Smart Citation
“…47 The significant relation between cognitive complaints and anxiety in MS patients is also in line with earlier findings and might be part of the above relation between anxiety and depression. 48 However, whether cognitive complaints contribute to anxiety or the other way around cannot be answered on the basis of our cross-sectional data. 25,35 Moreover, in a longitudinal study, 48 the authors showed that anxiety and fatigue were significant predictors of general cognitive concerns during a 2-year follow-up.…”
Section: Ms Population a Biological Hypothesis For The Overlap Betwementioning
confidence: 84%
“…Anxiety, along with depression and mental fatigue, accounts for a substantial part of the total variance of cognitive complaints in MS patients. 25,35 Moreover, in a longitudinal study, 48 the authors showed that anxiety and fatigue were significant predictors of general cognitive concerns during a 2-year follow-up. 48 However, whether cognitive complaints contribute to anxiety or the other way around cannot be answered on the basis of our cross-sectional data.…”
Section: Ta B L E 2 Means and Standard Deviations Of Psychological Qumentioning
confidence: 99%
“…Hence, in routine daily practice, depression and fatigue should also be assessed as per usual clinical care. Similarly, self-reported questionnaires about cognition in MS, might be useful in clinical studies but may not provide enough information about the cognitive domains affected to the examiner [ 59 ]. For example, the patient reported Multiple Sclerosis Neuropsychological Questionnaire (MSNQ-P) score may correlate with depression and anxiety but not with scores of cognitive tests [ 60 , 61 ].…”
Section: How To Measure?mentioning
confidence: 99%
“…Depression is a major mood disorder characterized by chronic low mood, disturbance of sleep and appetite, as well as feelings of inferiority, despair, and suicide [ 1 , 2 , 3 ]. Recent studies on the mechanisms of depression are mainly concentrated on the genetic, neural and biochemical factors, neuroendocrine function, electroencephalogram (EEG) dynamics, neuroimaging and psychosocial problems [ 4 ].…”
Section: Introductionmentioning
confidence: 99%